Pembuatan Pakan Ternak dari Limbah Tanaman Jagung di Desa Meranti Kecamatan Tapa Kabupaten Bone Bolango - Umbang Arif Rokhayati (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
This service activity was carried out in March 2023 in Meranti Village, Tapa District, Bone Bolango Regency. The purpose of this service is to provide knowledge that corn plant waste can be used as animal feed. The materials used in this service are corn plant waste as the main ingredient and EM4, rice bran and molasses as additional ingredients. The tools used in this service activity are chopping machines, plastic drums, tarpaulins and rubber as ropes. The results achieved from this community service activity are that the people of Meranti Village can understand the problems of animal feed and their treatment by utilizing corn plant waste, and can make fermented animal feed from corn plant waste.